Studies on diagnosis and treatment of trigeminal neuralgia - Ortiz González, Johanna Leticia; Almendariz Ormaza, Dafne Nayeli; Freire Rengel, Gerardo Francisco; Granja Carrión, Gerardo Antonio (Salud, Ciencia y Tecnología - Serie de Conferencias, 2023)
The studies carried out on Trigeminal Neuralgia are varied and their results have advanced in the identification of its characteristics, classification, diagnosis and treatment analysis. The review developed made it possible to identify the main characteristics that occur in trigeminal neuralgia in the patients analyzed. The different cases reflected in the investigations have allowed progress in their identification forms and the variation of treatments that favor their attention and control. Research agrees on the importance of magnetic resonance studies for diagnosis and the need for mastery by health personnel, for a correct diagnosis in patients that contributes to their prompt treatment. The research shows the advances achieved by health in the identification of trigeminal neuralgia and early care for patients.